PENGARUH DAN SUDUT KAMPUH PENGELASAN TERHADAP KEKERASAM DAN KERETAKAN PADA LAS SMAW DENGAN ELEKTRODA E7018 - Sasono, Djoko; Kusuma, Indra (MEKANIKA: Jurnal Teknik Mesin, 2015)
Pengaruh arus dan sudut kampuh Pengelasan Terhadap Kekerasan dan keretakan pada Las SMAW Dengan Elektroda E7018.â€Comparison journal with Joko Santoso, 2006. TM, FT, UNNES "Welding current Effect AgainstTensile Strength and Toughness Las SMAW with E7018 Electrodes" .Penelitian uses low alloy steel materials,materials treated with a variety of welding current 100 Ampere, 130 Ampere and 160 Amper using reverse polarityDC SMAW welding electrode E 7018 with a diameter of 3.2 mm. Seam type used is seam V with an angle of 60 Â°. The value of tensile strength and yield stress to specimen quality force tensile low alloy steel welding current 160Ampere group the highest compared with those variations welding current of 100 amperes and 130 amperes and rawmaterials group. Its value has increased by 44.84 MPa to values of tensile strength and 84 MPa for the yield stressvalue of the raw materials group. The value of the extension and increased cross-section reduction compared to thegroup and the group 130 100 Amper Amper, but decreased compared with those raw materials.This study aims to determine the effect of welding current against violence, the corner seam welds and cracks levels1,2 and 3 on the SMAW welding electrode E7018. This study uses a low alloy steel material treated wi th a variety ofwelding currents of 80 A and 180 A with a seam angle of 60 Â° and 80 Â°, using SMAW welding DC polarity inverted with E7018 electrode diameter of 3.2 mm. DC reverse polarity that the electrode holder is connected to the positive pole and the metal stem is connected tothe negative pole. Specimens carried hardness testing and cracking levels 1,2 and 3, Hardness of weld joint highestin the group of specimens of 60 Â° to 180 A which is worth 181 HB for angle of 80 Â° to 180 A and 181 HB, the lowe stvalue obtained angle of 80 Â° with 80 A whose value is 141 HB, to an angle of 60 Â° to 80 A HB 156 value from thedata above is taken the average - average, for the position of HAZ According to the results of this study concludedthat with the variation of the welding current is very influence in welding materials and therefore contributes toviolence. Keywords are current, angle, SMAW, violence, rift, E7018.